Prosperity and Prophecy in African Pentecostalism - Quayesi-Amakye, Joseph (Journal of Pentecostal Theology, 2011)
This essay discusses how prosperity is understood and articulated in Ghanaian Pentecostal prophetic circles. It seeks to show that in the peripheral prophetism of Pentecostalism, prosperity is perceived as the good life Christ offers those who believe in him. The good life is a religious and social quest of Ghanaians. The bad life is a privation of goodness in this life. Coping with the bad life has necessitated the patronage of Ghanaian prophetic services where rituals of transformation are employed to negotiate evil and suffering in the life of the faithful. Critical in the discussion is the role of the 'Other' who creates conditions of impoverishment for people and who justifies the necessity of prophetic negotiation. The paper also analyses the content of the bad life and finally attempts to show that Christ's parables in Luke 16 propose a guiding paradigm for conceiving prosperity as a tool for harmonious interhuman relations.
free
Keywords: CAUSALITY; EVIL; NEGOTIATION; PERIPHERAL PROPHETISM; PROSPERITY; THE 'OTHER'